Marshall’s syndrome in the practice of infection disease doctor and pediatrician (сlinical case) - I. V. Babachenko; N. S. Tian; M. A. Ivanova; E. V. Sharipova; T. L. Belikova (Журнал инфектологии)
On the basis of literary sources, modern ideas about Marshall syndrome in children are given, as well as the main clinical and laboratory criteria for the diagnosis of this syndrome. A clinical case of Marshall syndrome in a boy 3 years 6 months infected with human herpes virus type 6 is described. Differential diagnostic criteria of Marshall syndrome and active herpesvirus infections in children are presented on the example of a clinical case.